RETRACTED ARTICLE: Acid-modified CNT/Zinc Oxide nanowires based high performance broadband photodetector - K. Moatemsu Aier; Jay Chandra Dhar (Scientific Reports)
Abstract In this study, the authors have reported the impact of post-treatment via exposure to acid on single walled carbon nanotubes (SWNTs) thin film (TF) based SWNT/ZnO Nanowire (NW) broad band photodetector. The ZnO NWs were deposited on SWNT (with and without acid-treated) using a simple catalytic free process called glancing angle deposition (GLAD) technique. Acid-treated SWNT samples warranted the growth of high quality ZnO NWs over them. On fabricating photodetectors with the acid-treated ZnO NW/SWNT TF heterostructure (HS) gave better device performance as compared to the as-deposited ZnO NW/SWNT TF HS (without acid-treatment) sample. The acid-treated device showed a large responsivity (85.45 A/W), specific detectivity (0.859 × 1012 Jones) and with a low noise equivalent power of 3.9101 pW values. Moreover, the oxygen adsorption–desorption mechanism in SWNTs impacted the electrical resistance of the nanotubes which affected nanotube conductivity. The acid-treatment favoured relatively faster charge separation at the ZnO NW/SWNT heterojunction thus providing a fast device response (t rise  = 0.11 s, t fall  = 0.39 s at + 5 V). The fabricated acid-treated device showed good broad band detection (250 nm-750 nm) which was explained with respect to the optical absorption profile of the sample.